Kajian Nilai Estetis dan Simbolis Ukiran Masjid Mantingan Jepara - abdulloh eizzi irsyada (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
The Mantingan Mosque is an old mosque founded by a Duke of Jepara, Sultan Hadlirin and his wife Ratu Kalinyamat in 1481 Saka or 1559 AD. Besides having beauty in the architecture of the building, it also has ancient ornaments patterned with flowers, plants, animals and others that are beautifully carved around its walls. The diversity of motifs, shapes and patterns of each carving makes researchers interested in knowing what are the aesthetic and symbolic values ​​contained in each carving ornament on the walls of the Mantingan Jepara mosque. Aesthetic values ​​are represented in a carving media which is then designed to be fully carved into beautiful, intricate,